Real-time testing of energy storage systems in renewable energy applications - Caruana, C.; Sattar, A.; Al-Durra, A.; Muyeen, S.M. (2015)
Energy storage systems provide a promising solution for the renewable energy sector to facilitate large-scale grid integration. It is thus very important to explore means to validate their control scheme and their behaviour in the intended application before actual commissioning. This paper presents a reduced-scale hardware-in-the-loop simulation for initial testing of the performance of energy storage systems in renewable energy applications. This relieves the need of selecting and tuning a detailed model of the energy storage element. A low-power test rig emulating the storage element and the power converter is interfaced with a real time digital simulator to allow dynamic experimental tests under realistic conditions. Battery energy storage for smoothing the output power of a variable speed wind turbine is considered in this paper; however the proposed test methodology can be easily adapted for other storage elements in renewable energy, distributed generation and smart grid applications. The proposed HIL simulation is detailed and the experimental performance is shown.